Novel-male induced pregnancy failure in mice: effects on implantation, luminal area and e-cadherin - Rajabi, Nazanin (My University, 2012)
Adhesion of the blastocyst to the uterine wall is a highly sensitive phenomenon referred to as implantation. Novel-males are capable of disrupting the success of this process (the Bruce effect). A leading hypothesis invokes the transfer of estradiol from the male to the female via urine. This estradiol has direct effect on the uterus which may include morphology and molecular dynamics. Estradiol has been related to closure of the uterus around the blastocyst during implantation, which may assist in bringing the blastocyst close to the uterine wall for strong adhesion. E-cadherin, a cellular adhesion molecule, is found on both blastocyst and uterine surfaces and has been suggested to be involved in their interaction during implantation. Estradiol has been observed to reduce e-cadherin expression in hormonally sensitive tissues like the mammary glands, ovaries and uteri. Here, male-induced disruption of implantation was examined across days 2-8 of gestation. Luminal area was quantified in isolated and male-exposed females as a measure of extent of luminal closure. This area was larger in male-exposed animals. E-cadherin was found to have reduced expression on luminal epithelial cells. I suggest that the reduction in e-cadherin may lead to weaker attachment of the blastocyst to the uterine wall as well as reduced adhesion between opposing uterine walls leading to the “opening” of the uterus observed in male exposed animals. Together, these data may in part explain the blastocyst implantation failure observed in male-exposed animals during the Bruce effect.
Keywords: Bruce Effect; E-Cadherin; Implantation Failure; Estrogen; Luminal Area; Cellular and Molecular Physiology; Endocrinology; Cellular and Molecular Physiology